2015
DOI: 10.17719/jisr.20153710663
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Employee Empowerment on Innovation: A Survey on Isparta and Burdur Organized Industrial Zones

Abstract: This study has analyzed, by examining the relationship between empowerment and innovativeness which are significant concepts for organizations, how empowerment efforts affect innovativeness, and how behavioural, psychological, and social and structural dimensions of empowerment affects innovativeness. As a result of these examinations, all the hypotheses which comprised our research have been accepted. In other words, it has been concluded that the behavioural, psychological, and social and structural empowerm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 11 publications
3
14
0
2
Order By: Relevance
“…This result also implies that the employees hold and perceived all the cognitions of psychological empowerment in the Jordanian hotels which in turn leads them to be more able go through innovation performance effectively. This result was supported with previous researches, which confirmed a significant relationship between psychological empowerment and innovation performance (Spreitzer 1995;Bolat 2008;Kahreh et al, 2011;Köksal, 2011;Bhatnagar, 2012;and Uzunbacak, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This result also implies that the employees hold and perceived all the cognitions of psychological empowerment in the Jordanian hotels which in turn leads them to be more able go through innovation performance effectively. This result was supported with previous researches, which confirmed a significant relationship between psychological empowerment and innovation performance (Spreitzer 1995;Bolat 2008;Kahreh et al, 2011;Köksal, 2011;Bhatnagar, 2012;and Uzunbacak, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The research's results argued that when structural empowerment and psychological empowerment are merged together as a whole, the influence of empowerment on employees' innovation performance shows a higher level (R 2 = 0.473, p = 0.000), which distinguishes this research from other researches were conducted. This result was supported by Uzunbacak (2015) who indicated that employees are appreciated the efforts of empowerment, participate in management, have the authority to make decisions and to produce new ideas and that managers attempt to create an environment which will facilitate employees' creativity and innovativeness encourages employees to behave innovatively. In this created environment (structural empowerment), the employee will feel empowered and be able to produce and implement new ideas (Köksal, 2011).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations